Method of Lighting Performance Assessment in Heritage Area: Case Study of Kayutangan Pedestrian Corridor - Sayekti, Sirly Intan; Wikantiyoso, Respati; Bonifacius, Nurhamdoko (Proceedings of International Conference of Graduate School on Sustainability, 2025)
Outdoor lighting serves as a crucial element for visibility and plays a vital role in creating a comfortable and safe atmosphere in public spaces, particularly along pedestrian corridors. Lighting is an integral part of urban design that can enhance the identity of an area and support public activities, especially at night. This article presents a literature review aimed at identifying the most suitable method for evaluating outdoor lighting performance along the Kayutangan pedestrian corridor in Malang, following the revitalization of the Kayutangan Heritage Corridor. This review employs a literature-based approach to establish a foundation for future research on measuring light intensity at multiple strategic points along the pedestrian area. The findings from this review aim to identify methods for assessing the quality of existing lighting and determine whether the lighting meets SNI, CIE, and IESNA standards, while fostering a positive public perception. This study will further support research that selects sample measurement points based on the function of active spaces within the Kayutangan Heritage Corridor. The literature review provides insights into how outdoor lighting can support or hinder public interaction at night. The results of this review are expected to provide a comprehensive understanding of the standards and measurements applied to outdoor lighting in public areas, particularly the pedestrian zones within the Kayutangan Heritage Corridor.